The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/all.13076
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for hereditary angioedema with normal C1-INH and specific mutations in theF12gene (HAE-FXII)

Abstract: Hereditary angioedema with normal C1 esterase inhibitor and mutations in the F12 gene (HAE-FXII) is associated with skin swellings, abdominal pain attacks, and the risk of asphyxiation due to upper airway obstruction. It occurs nearly exclusively in women. We report our experience treating HAE-FXII with discontinuation of potential trigger factors and drug therapies. The study included 72 patients with HAE-FXII. Potential triggers included estrogen-containing oral contraceptives (eOC), hormonal replacement the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 19 publications
1
58
0
13
Order By: Relevance
“…Tranexamic acid is a competitive inhibitor of the lysine‐binding sites in the kringle domains of PLG and plasmin. It is effective in various degrees in the long‐term prophylaxis in HAE‐C1‐INH, in HAE‐FXII, and in HAE‐PLG as mentioned in this article. The exact mode of action of antifibrinolytics in HAE, however, is not fully understood.…”
Section: Discussionmentioning
confidence: 88%
“…Tranexamic acid is a competitive inhibitor of the lysine‐binding sites in the kringle domains of PLG and plasmin. It is effective in various degrees in the long‐term prophylaxis in HAE‐C1‐INH, in HAE‐FXII, and in HAE‐PLG as mentioned in this article. The exact mode of action of antifibrinolytics in HAE, however, is not fully understood.…”
Section: Discussionmentioning
confidence: 88%
“…59 Hereditary angioedema with normal C1 inhibitor and specific mutations in the F12 gene (HAE-FXII) exists, and recommendations for treatment were given from a personal experience in 72 patients. 60 Idiopathic non-histaminergic acquired angioedema (InH-AAE) is a rare disease for which there are no available laboratory parameters to clearly define the disorder. A literature review was performed, and omalizumab was found to induce a complete remission in the 20 patients treated.…”
Section: Drug Allergymentioning
confidence: 99%
“…22 and off label use has been reported. 9,25 No data are available concerning differences in clinical management, treatment response, or prognosis between patients with variants in F12 (FXII-HAE) and variant-negative patients (U-HAE).…”
Section: How Is the Cost Effectiveness Of Alternative Diagnostic Methmentioning
confidence: 99%